A Fe3+-crosslinked pyrogallol-tethered gelatin adhesive hydrogel with antibacterial activity for wound healing. (4th May 2020) - Han, Ning; Xu, Ziyang; Cui, Chunyan; Li, Yuan; Zhang, Dongfei; Xiao, Meng; Fan, Chuanchuan; Wu, Tengling; Yang, Jianhai; Liu, Wenguang
Abstract : A tunicate-inspired gelatin-based hydrogel prepared by a simple mixing method, exhibits strong adhesion and antibacterial capacity, and facilitates wound healing. Abstract : In this work, a tunicate-inspired gelatin-based hydrogel is prepared by simply mixing 2, 3, 4-trihydroxybenzaldehyde (THB)-tethered gelatin solution with a small amount of Fe 3+ ions via the Schiff-base reaction and simultaneous formation of hexavalent Fe-complexes. The resulting hydrogel (termed GelTHB-Fe) exhibits not only tunable gelation time, rheological properties and self-healing ability by adjusting the composition, but also robust adhesion to a variety of materials, with an average adhesion strength of 136.7 kPa, 147.3 kPa, 153.7 kPa, 92.9 kPa, and 56.5 kPa to PMMA, iron, ceramics, glass and pigskin, respectively. Intriguingly, the pyrogallol moieties impart an antibacterial activity to the GelTHB-Fe hydrogel, which is shown to reduce infection and promote wound healing in a diabetic rat model. This GelTHB-Fe hydrogel holds great potential as a promising tissue adhesive.